DCT/IDCT filter design for ultrasound image filtering - Honarvar Shakibaei Asli, Barmak; Flusser, Jan; Zhao, Yifan; Erkoyuncu, John Ahmet; Roy, Rajkumar (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this paper, a new recursive structure based on the convolution model of discrete cosine transform (DCT) for designing of a finite impulse response (FIR) digital filter is proposed. In our derivation, we start with the convolution model of DCT-II to use its Z-transform for the proposed filter structure perspective. Moreover, using the same algorithm, a filter base implementation of the inverse DCT (IDCT) for image reconstruction is developed. The computational time experiments of the proposed DCT/IDCT filter(s) demonstrate that the proposed filters achieve faster elapsed CPU time compared to the others. The image filtering and reconstruction performance of the proposed approach on ultrasound images are presented to validate the theoretical framework.
Keywords: Wiener filters; Ultrasonic imaging; Finite impulse response filters; Convolution; Filtering; Filtering algorithms; Fetus